Efficient RNA interference method during caste differentiation with hormone treatment in the termite Reticulitermes speratus (Isoptera: Rhinotermitidae) - Suzuki, Ryutaro; Masuoka, Yudai; Suzuki, Ryohei H.; Maekawa, Kiyoto (Frontiers in Insect Science, 2023)
Unveiling the proximate mechanism of caste differentiation is crucial for understanding insect social evolution, and gene function analysis is an important tool in this endeavor. The RNA interference (RNAi) technique is useful in termites, but its knockdown effects may differ among species. One of the most important model species in the field of termite sociogenomics is Reticulitermes speratus Kolbe (Isoptera: Rhinotermitidae). Presoldier and worker differentiation of this species can be artificially induced by juvenile hormone and 20-hydroxyecdysone application, respectively. However, appropriate RNAi technique of genes expressed during caste differentiation has never been considered. To clarify this issue, first, we injected nine different volumes of nuclease-free water (NFW, 0–404.8 nL) into workers and found that survival and caste differentiation rates were strongly reduced by the application of the top three largest volumes. Second, we injected double-stranded (ds) RNA of ecdysone receptor homolog (RsEcR) (2.0 µg/151.8 nL NFW) into workers with hormone treatments. The expression levels of RsEcR were significantly reduced at 9 days after dsRNA injection. RsEcR RNAi strongly affected both molting events during presoldier and worker differentiation induced by hormone treatments. The present results highlight the need for caution regarding injection volumes for RNAi experiments using hormone treatments. We suggest that the injection of dsRNA solution (2 µg; approximately 100–200 nL) is suitable for RNAi experiments during caste differentiation induced by hormone application in R. speratus.